“The targets…are driving the agenda and that probably needs to change”: stakeholder perspectives on HIV partner notification in sub-Saharan Africa - McGowan, Maureen; Bärnighausen, Kate; Berner-Rodoreda, Astrid; McMahon-Rössle, Shannon A.; Mtaita, Caroline; Mauti, Joy; Neuhann, Florian (BMC public health, 2024)
Background: Voluntary assisted partner notification (VAPN) in HIV contact tracing is a globally recommended strategy to identify persons who have been exposed to HIV and link them to HIV testing and follow-up. However, there is little understanding about how VAPN is experienced by stakeholders in sub-Saharan African (SSA) contexts. We conducted a multi-level and multi-national qualitative analysis evaluating stakeholder perspectives surrounding VAPN implementation to inform the development of future VAPN policies. Method: We conducted in-depth interviews (IDIs) with VAPN stakeholders at global (n = 5), national (n = 6), and community level (n = 4) across a total of seven SSA countries. Eligible participants were ≥ 18 years old and had experience developing, implementing, or overseeing VAPN policies in SSA. We sought to understand stakeholder’s perspectives on policy development, implementation, and perceived outcomes (barriers and facilitators). Interviews were audio recorded, transcribed, and analyzed thematically using a combination of inductive and deductive approaches. Results: Between December 2019 and October 2020 we conducted 15 IDIs. While participants agreed that VAPN resulted in a high yield of people newly diagnosed with HIV; they noted numerous barriers surrounding VAPN implementation across global, national, and community levels, the majority of which were identified at community level. Barriers at global and national level included high target setting, contradictory laws, and limited independent research disenfranchising the experiences of implementing partners. The barriers identified at community level included client-level challenges (e.g., access to healthcare facilities and fear of adverse events); healthcare worker challenges (e.g., high workloads); limited data infrastructure; and cultural/gender norms that hindered women from engaging in HIV testing and VAPN services. In response to these barriers, participants shared implementation facilitators to sustain ethical implementation of VAPN services (e.g., contact tracing methods) and increase its yield (e.g., HIV self-testing integrated with VAPN services). Conclusion: Overall, stakeholders perceived VAPN implementation to encounter barriers across all implementation levels (global to community). Future VAPN policies should be designed around the barriers and facilitators identified by SSA stakeholders to maximize the implementation of (ethical) HIV VAPN services and increase its impact in sub-Saharan African settings.
Gesehen am 25.07.2024